2019
DOI: 10.1111/jfpe.13163
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of drying methods on drying efficiency and physicochemical quality of okra (Abelmoschus esculentus) cultivated in China

Abstract: Okra (Abelmoschus esculentus) is difficult to preserve after harvest. If not properly dried, because of its high moisture content, which will reduce the product value of okra and the value of nutrition. In this study, the effects of vacuum freeze‐drying (VFD), ultrasonic pretreatment assisted vacuum drying (UPVD), and ultrasonic combined vacuum drying (UCVD) are compared and analyzed in terms of the drying characteristics effects and the physicochemical qualities of okra were studied. Compared with the drying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
(60 reference statements)
2
9
0
Order By: Relevance
“…Hereafter, the effective diffusivity factors ( D 0 ) present a significant variation between samples dried by ultrasonically convective, microwave drying, hot‐air convective, freeze, infrared drying processes ( p < .05). Interestingly, the obtained activation energy values ( E a ) were comparable to these found for other drying fruit and legume slices (Jebri et al., 2019; Wang et al., 2019; Zhu & Shen, 2014).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Hereafter, the effective diffusivity factors ( D 0 ) present a significant variation between samples dried by ultrasonically convective, microwave drying, hot‐air convective, freeze, infrared drying processes ( p < .05). Interestingly, the obtained activation energy values ( E a ) were comparable to these found for other drying fruit and legume slices (Jebri et al., 2019; Wang et al., 2019; Zhu & Shen, 2014).…”
Section: Resultssupporting
confidence: 83%
“…This can be attributed to that ultrasonic process can generate microchannels to improve mass transfer, and internal moisture removal easier as suggested by Wang et al. (2019). According to Yildiz and Izli (2019), the ultrasound pretreatment of quince slices has a positive effect on the structure of the dried products.…”
Section: Resultsmentioning
confidence: 87%
“…Some investigations indicated that okra powder had antioxidant activities, such as 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl radical scavenging capacity, and oxygen radical absorbance capacity (ORAC). In addition to flavonoids, proteins, and polyphenols, , OPs are considered as one of the important compounds in the antioxidant activities.…”
Section: Bioactivities Of Opsmentioning
confidence: 99%
“…Okra can be consumed fresh, as a snack, or processed further as a cooked vegetable or added into salads, soups, and stews. Okra contains high nutritional value, acts as a good source of protein, dietary fiber, carbohydrate, rich in polyphenol, vitamins (A and C), minerals (calcium, magnesium, and potassium), and other bioactive compounds (Aamir & Boonsupthip, 2017; Pendre et al, 2012; Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Drying is one storage method that has the capability of extending the consumption period of a food product, and one of the ways that has been found effective to reduce the moisture content of okra to be safe for storage. Several drying methods have been reported to be utilized to dry okra, including hot air, microwave, and freeze‐drying (Aamir & Boonsupthip, 2017; Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%